STRUCTURE AND FUNCTIONS OF SOCIAL SUPPORT IN A GROUP OF MOROCCAN IMMIGRANTS - Hernández Plaza, Sonia; Pozo Muñoz, Carmen; Alonso Morillejo, Enrique; Martos Méndez, Mª José (Anales de Psicología / Annals of Psychology, 2005)
The aim of the present investigation is to describe the structural and functional characteristics of the social support system in a group of Moroccan immigrants, and to analyze their relation with subjective well-being. The sample of the study is composed of 100 Moroccan immigrants who answered the ASSIS social support interview (Barrera, 1980), the satisfaction with life scale (Diener et al., 1985) and a measure of ethnic prejudice perception. Results show that relationships with natives are scarce in Moroccans’ social networks. Interpersonal ties with other immigrants are the main source of informative, material and emotional support for this group. Satisfaction with emotional support provided by autochtonous people, satisfaction with informative support and sufficiency of support given by other immigrants, as well as ethnic prejudice perception are the predictor variables of Moroccans’ subjective well-being. These results therefore confirm that the specific social support dimensions with a positive effect on immigrants’ subjective well-being are the funcional ones, and vary depending on the origin, autochtonous vs. foreigner, of the support provider.